Transforming WhatsApp and Zoom into Religious Space: A Digital Ethnography of an Online Meditation Community in Indonesia - Wirawan, Wirawan; Sukandar, Rudi (JURNAL KOMUNIKASI INDONESIA, 2024)
Drawing on an online meditation community mentored by Samanera Abhisarano in Indonesia, this study explores how the members use digital media to engage in religious practices and teachings. The data were collected through multisited digital ethnographic fieldwork conducted from December 2021 to July 2022. During this period, we immersed ourselves in the WhatsApp group and the Zoom virtual room of the community. In addition to participating in their online activities and interviewing five community members remotely, we conducted on-site fieldwork at the temple where the mentor lives and organized a face-to-face in-depth interview with him. Employing Hjarvard’s theory of mediatization of religion, we analyzed how Buddhist teaching and practices were mediatised through the intensive use of digital media in religious environments. We argue that digital media have, to some extent, transformed the routine of this community in terms of performing religious activities. The finding supports Hjarvard’s argument that mediatization of religion is a process in which the media have taken over some roles of religious authority and transformed the way society interacts with religion.